An Experimental Measurement Through Folk Therapy to Strengthen the Immunity After Confirmed COVID-19 (Journal of Pharmaceutical Negative Results, 2022)
This study is to perform experimental measurements through folk therapy to strengthen the physical immunity after confirmed COVID-19. The survey was conducted from May 8 to July 10, 2021. The experimental group applied to the information system was classified as 46 people, and the control group not applied was classified as 46 people. In this study, a total of 92 people used the survey The process of time change of symptoms of COVID-19 was analyzed by a t-test. The effect of applying folk remedies was measured on 8, 16, 24, and 32 days before and after applying folk remedies for symptoms of COVID-19. The results of this study were as follows. Firstly, in terms of age, 54.3% of the experimental group was significantly higher than 34.8% of the control group at the age of 60 or older(X2=7.51, p<.05). Secondly, the residual cough decreased significantly after application compared to before folk therapy(t=5.21, p<.05). Thirdly, the residual cough continued to decrease significantly after 8 days than before the experiment. The results were confirmed that the folk remedies applied in this study were effective. The research derived from this results is expected to contribute to alleviating respiratory symptoms